2022
DOI: 10.2298/tsci200830208s
|View full text |Cite
|
Sign up to set email alerts
|

Thermal management analysis of PCM integration in building using a novel performance parameter - PCM effectiveness index

Abstract: Integration of phase change material (PCM) in walls and roof of a building is done to augment human comfort at places where variation of local diurnal temperature of ambient air is extensive. An exhaustive tool to study on year-round thermal effect due to solar radiation falling on a building is generally required to identify the correct PCM and the portion of a year that warrants better thermal management. The transient behavior associated with PCM heat transfer through building roof and wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among selected studies most used ANSYS Fluent module, only two reported using ANSYS CFX. Regarding the time scale of modelling only one publication described simulation over one year period [10], most of others used smaller time scale -a day [11]- [13], a week [14], a month [15]- [20]. Other 15 publication used a time scale less than a day.…”
Section: Ansys Usage For Modeling Heat Transfer In Phase Change Mater...mentioning
confidence: 99%
See 2 more Smart Citations
“…Among selected studies most used ANSYS Fluent module, only two reported using ANSYS CFX. Regarding the time scale of modelling only one publication described simulation over one year period [10], most of others used smaller time scale -a day [11]- [13], a week [14], a month [15]- [20]. Other 15 publication used a time scale less than a day.…”
Section: Ansys Usage For Modeling Heat Transfer In Phase Change Mater...mentioning
confidence: 99%
“…8 of studies explored PCM in HVAC systems -ventilation systems [11], [12], [26]- [28], [34], [35], [42], heat exchangers [20], [25], [30]- [33], [36], [38] and other elements [20]; other 31 publications focused on walls [10], [13], [15], [17], [19], [21]- [24], [37], [39], [40], [43], [44], roofs [14], [18], [29], [37], floors [24], windows ( [41]). In 20 studies models were validated using experimental data [10]- [12], [14], [16], [17], [20], [22], [25]- [27], [29], [31], [32], [34]- [38], [40], 1 used analytical validation [45], 4 based validation on findings in other studies in scient...…”
Section: Ansys Usage For Modeling Heat Transfer In Phase Change Mater...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal management analysis of PCM integration in building using a novel performance parameter-PCM effectiveness index [13] Year Room Wall, roof Numerical analysis of nanomaterial-based sustainable latent heat thermal energy storage system by improving thermal characteristics of phase change material [14] Seconds Element Wall, floor Simulation of a Trombe wall with a number of semicircular fins placed on the absorber plate for heating a room in the presence of nano-PCM [15] Hour Room Wall Numerical thermal evaluation of laminated binary microencapsulated phase change material drywall systems [16] Month Room Wall…”
Section: Literature Review Of Pcm Numerical Modelingmentioning
confidence: 99%
“…The PCM performance in wall panels was evaluated using the method adopted from Selvaraju et al [46], as described in equations ( 1) and ( 2). The energy performance evaluated for a wall panel under Malaysia weather conditions is given in table 8.…”
Section: Effect Of Pcm On Energy Performancementioning
confidence: 99%